Ayurvedic Management of Anxiety Induced Insomnia (International Journal of Ayurveda and Pharma Research, 2024)
The extremely busy lifestyle has significantly impacted both the physical and mental health of individuals. Discussing mental health remains a stigma in society, profoundly affecting individuals' psyche. A male patient reported to the outpatient department with symptoms of anxiety, over thinking, disturbed sleep, body ache, fatigue, poor digestion, and frequent headaches for the past ten months. His score on the Hamilton Anxiety Rating Scale (HAM-A) was 30, indicating moderate to severe anxiety, and his score on the Pittsburgh Insomnia Severity Index (PSQI) was 17, classifying him as a poor sleeper. The patient underwent 42 days of Ayurvedic treatment, which included Panchakarma therapy and internal medications. The Panchakarma therapy consisted of Abhyanga with Matra Basti, Shirodhara, and Pratimarsha Nasya using Bala Ashwagandhadi oil. The internal medications included Manasmitra Vataka, Chitrakadi Vati, and Kalyanak Ghrita. After 42 days of treatment, the patient's HAM-A score decreased to 11, and the PSQI score dropped to 6. The patient reported a renewed sense of well-being and enthusiasm for work after a long time.